2020
DOI: 10.1128/mbio.00076-20
|View full text |Cite
|
Sign up to set email alerts
|

A Solution to Antifolate Resistance in Group B Streptococcus : Untargeted Metabolomics Identifies Human Milk Oligosaccharide-Induced Perturbations That Result in Potentiation of Trimethoprim

Abstract: Adjuvants can be used to potentiate the function of antibiotics whose efficacy has been reduced by acquired or intrinsic resistance. In the present study, we discovered that human milk oligosaccharides (HMOs) sensitize strains of group B Streptococcus (GBS) to trimethoprim (TMP), an antibiotic to which GBS is intrinsically resistant. Reductions in the MIC of TMP reached as high as 512-fold across a diverse panel of isolates. To better understand HMOs’ mechanism of action, we characterized the metabolic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

7
3

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 78 publications
1
35
0
Order By: Relevance
“…It has been recently demonstrated that when exposed to HMOS, GBS becomes sensitive for trimethoprim, an antibiotic to which these bacteria are normally resistant. A significant decrease in metabolic pathways related to membrane construction was observed (175). Furthermore, HMOS were able to sensitize GBS to several antibiotics, such as erythromycin, gentamycin and clindamycin.…”
Section: Pathogen Bindingmentioning
confidence: 97%
“…It has been recently demonstrated that when exposed to HMOS, GBS becomes sensitive for trimethoprim, an antibiotic to which these bacteria are normally resistant. A significant decrease in metabolic pathways related to membrane construction was observed (175). Furthermore, HMOS were able to sensitize GBS to several antibiotics, such as erythromycin, gentamycin and clindamycin.…”
Section: Pathogen Bindingmentioning
confidence: 97%
“…Briefly, 300 µL of dry ice cooled methanol was added to individual culture medium samples and incubated overnight at -80°C; individual samples were spun down to remove proteins and subsequent supernatant used for analyses. Samples were separated and analysed using reverse-phase liquid chromatography connected to a a Thermo Scientific Q Exactive HF (LC-Hybrid Quadrupole-Orbitrap MS/MS) instrument using positive ion mode MS [89][90][91]. MS raw data were imported, processed, normalized, and reviewed using Progenesis QI v.2.1 (Non-linear Dynamics, Newcastle, UK).…”
Section: Experiments Design 4 -Global Untargeted Metabolomicsmentioning
confidence: 99%
“…Each sample was then spun down to remove proteins and to aspirate the supernatant for analysis. Reverse-phase liquid chromatography was used, connected to a Thermo Scientific Q Exactive HF (LC-Hybrid Quadrupole-Orbitrap MS/MS) instrument using positive ion mode MS [ 26 , 27 , 28 ]. The data were thus imported, processed and normalized in Progenesis QI v.2.1 (Non-linear Dynamics, Newcastle, UK).…”
Section: Methodsmentioning
confidence: 99%